The Implementation of Life Skill Education (Lse) Learning In Strengthening Character Education In Bone District - Sarifa Suhra (Lembaga Sembilan Tiga Community, 2022)
This paper aims to reveal the suitability of Life Skills Education learning with the 2013 curriculum which is able to strengthen the character education of students in schools designated by the local government as Unicef ​​piloting schools in Bone Regency. This research is located in SMP Negeri 2 Ajangale so it includes field research using a qualitative approach. The research instrument used an interview guide and google form. The results showed that; The formulation of Life Skills Education Learning Implementation that is Relevant to the 2013 Curriculum is based on six core curriculum components, namely, curriculum objectives, Program/Material Content and Structure, Learning media, methods, and evaluation. These characteristics include; the ability to self-regulate, be creative, and critically thinking, make decisions, negotiate, cooperate, solve problems, participate, able to manage stress and emotions, be resilient, able to survive, empathize with communication, and appreciate differences..